Substrate Stiffness Determines the Establishment of Apical-Basal Polarization in Renal Epithelial Cells but Not in Tubuloid-Derived Cells - Hagelaars, Maria J.; Yousef Yengej, Fjodor A.; Verhaar, Marianne C.; Rookmaaker, Maarten B.; Loerakker, Sandra; Bouten, Carlijn V. C. (Frontiers in Bioengineering and Biotechnology, 2022)
Mechanical guidance of tissue morphogenesis is an emerging method of regenerative medicine that can be employed to steer functional kidney architecture for the purpose of bioartificial kidney design or renal tissue engineering strategies. In kidney morphogenesis, apical-basal polarization of renal epithelial cells is paramount for tubule formation and subsequent tissue functions like excretion and resorption. In kidney epithelium, polarization is initiated by integrin-mediated cell-matrix adhesion at the cell membrane. Cellular mechanobiology research has indicated that this integrin-mediated adhesion is responsive to matrix stiffness, raising the possibility to use matrix stiffness as a handle to steer cell polarization. Herein, we evaluate apical-basal polarization in response to 2D substates of different stiffness (1, 10, 50 kPa and glass) in Madin Darby Canine Kidney cells (MDCKs), a classic canine-derived cell model of epithelial polarization, and in tubuloid-derived cells, established from human primary cells derived from adult kidney tissue. Our results show that sub-physiological (1 kPa) substrate stiffness with low integrin-based adhesion induces polarization in MDCKs, while MDCKs on supraphysiological (>10 kPa) stiffness remain unpolarized. Inhibition of integrin, indeed, allows for polarization on the supraphysiological substrates, suggesting that increased cellular adhesion on stiff substrates opposes polarization. In contrast, tubuloid-derived cells do not establish apical-basal polarization on 2D substrates, irrespective of substrate stiffness, despite their ability to polarize in 3D environments. Further analysis implies that the 2D cultured tubuloid-derived cells have a diminished mechanosensitive capacity when presented with different substrate stiffnesses due to immature focal adhesions and the absence of a connection between focal adhesions and the cytoskeleton. Overall, this study demonstrates that apical-basal polarization is a complex process, where cell type, the extracellular environment, and both the mechanical and chemical aspects in cell-matrix interactions performed by integrins play a role.